Pendidikan Anti Korupsi sebagai Tindakan Preventif Perilaku Koruptif - Dhevy Setya Wibawa; Murniati Agustian; M Tri Warmiyati (Muqoddima Jurnal Pemikiran dan Riset Sosiologi, 2021)
Corruption has already become a part of culture in the society. Corruption happens in both government and private sector; the most concerning thing is the involvement of the head of institutions which supposed to be a role model for young generation. There are a lot of things have been done to decrease our corruption cases from law perspective, unfortunately a preventive attempt from education perspective has not much been applied. Anti-corruption education is a preventive effort to build self-awareness and integrity against corruptive behavior. The research objective was to obtain an overview of whether anti-corruption education could develop students’ sensitivity and concern for corruption issues. The research method used is action research through collective self-reflection which is integrated with the student-centered learning approach carried out in groups and is achieved through reflective critical action of group members as individuals whose learning outcomes are measured. There were 25 university students from 7 faculties participated in this research. The findings showed that students were able to identify corrupt actions based on personal and group experiences. Participants were also able to identify the impact of time corrupt behavior on individuals and institutions. In the reflection stage, participants reveal the values of integrity such as honesty, responsibility and consistency between attitudes and behavior, as well as religious values which believed to be a fortress against corrupt actions. The action research is followed up by making an action plan to become a person with an integrity and in managing anti-corruption student organizations.